Dynamics of gender justice in the state’s negation of victims of sexual violence - Meiliana, Trinita; Mayrudin, Yeby Ma'asan (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
This article examines the complexities surrounding the construction and understanding of gender justice for women victims of sexual violence who are overlooked by the state. Addressing the need for justice for these victims is vital, as women frequently face discriminatory treatment that can lead to victim-blaming. The study uses a qualitative, phenomenological approach based on Creswell's framework, emphasizing the interpretation of 'Gender Justice' through the experiences of key informants, which highlight varied perspectives influenced by their life experiences. The research primarily incorporates Gender and Feminism Theory and Gender Justice to analyze the issue. Key findings reveal a lack of empathy and insufficient training among law enforcement regarding sexual violence cases, along with stigma and intimidation from officers, coupled with inadequate legal protections for victims. Additionally, the legal bureaucracy is convoluted and unresponsive, making the current legal system ineffective in achieving gender justice and often neglecting the rights and needs of sexual violence survivors. These results indicate that the existing legal and governmental frameworks fail to provide equitable gender justice, often overlooking the requirements and rights of survivors. Legal certainty should be clear and consistent; however, in reality, victims often do not experience this certainty. The injustices faced by survivors stem not only from legal shortcomings but also from entrenched discriminatory and patriarchal social norms.